Educational Effects of Early or Later Secondary School Tracking in Germany - Andrea Maria Mühlenweg (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper examines educational outcomes of pupils selected to secondary school types by different tracking regimes in a German state: Pupils are alternatively streamed after fourth grade or after sixth grade. Regression results indicate that, estimated on the mean, there are no negative effects of later tracking on educational outcomes in the middle of secondary school. Positive effects are observed for pupils with a less favorable family background. Quantile regressions reveal that the estimated effects of later tracking are positive for the lower quantiles but decrease monotonically over the conditional distribution of test scores.
Keywords: I28; I21; 330; education; segregation; immigration; school effects; Bildungsniveau; Schulauswahl; Segregation; Migranten; Deutschland